Biopolymer-based encapsulation of Adriatic Ulva biomass bioactives: environmentally friendly technological advance in marine functional ingredients - Ćujić Nikolić, Nada; Mutavski, Zorana; Drakulović, Dragana; Marković, Smilja; Vulić, Jelena; Bigović, Dubravka; Šavikin, Katarina (Frontiers in Marine Science, 2025)
IntroductionThe genus Ulva, abundant in the Adriatic Sea, serves as a sustainable source of bioactive compounds, including polyphenols and natural pigments such as chlorophylls and carotenoids, with potential applications in the food, nutraceutical, pharmaceutical, and environmental protection sectors. However, their low chemical stability, bioavailability, and undesirable sensory properties limit practical use.MethodsThis study explored encapsulation methods for Ulva spp. extract using spray-drying and freeze-drying techniques, with biopolymer carriers such as maltodextrin as a conventional option and polydextrose as an innovative alternative, to enhance the stability and functionality of the bioactive compounds. Technological properties, including encapsulation yield, moisture content, bulk and tapped densities, rehydration time, and encapsulation efficiency, were evaluated, along with FTIR, DSC, and HPLC analyses.Results and discussionComparative results showed that, while the spray-dried extract without a carrier achieved the highest polyphenolic encapsulation efficiency of 86.5%, polydextrose was more effective than maltodextrin in protecting total carotenoids and lutein. Spray-dried powders exhibited greater moisture reduction and improved powder properties than freeze-dried powders, which rehydrated faster and maintained good thermal stability up to 240°C. Antioxidant assays (DPPH, ABTS, RP) showed similarly high activity across all formulations, indicating that the functional compounds were preserved regardless of the encapsulation method. These findings demonstrate that combining suitable encapsulation techniques with tailored biopolymer carriers enhances the stability, bioactivity, and handling of Ulva-derived bioactive compounds. This approach promotes the valorization of underutilized macroalgal biomass within blue biotechnology, aligns with green and circular bioeconomy principles, and offers promising pathways for developing innovative marine-derived functional ingredients.